Kesalahan Jenayah Sihir: Analisa Seksyen 152 Perintah Kanun Hukuman Jenayah Syariah Brunei Darussalam = Witchcraft Crime: An Analysis Section 152 of the Syariah Penal Code Order Brunei Darussalam) - Mahyuddin, Ismail; Zulfakar, Ramlee; Jahid, Sidekk; Mohd. Jim, Hamzah; Zainal Abidin, Kusmin; Siti Aisyah, Romli (Department of Southeast Asian Studies, University of Malaya, 2017)
Among the biggest challenges to eradicate witchcraft is difficult to determine the existence of a crime (ifeal jana'aa ) and criminal intent (qasad jana'aa) by witch. Witchcraft is not only difficult to detect, the outcome upon its targeted victim is also hardly visible. This research aims to describe practical methods to disclose the metaphysical aspects by analyzing the materials and methods that have been used. The concept of 'effects from an act' will also being highlighted to help us to identify relations between crime (فعل جناءى ) and criminal intent (qasad jana'aa). This approach could open a new dimension to the legal system in relation to the implementation of section 152 of the Syariah Penal Code Order of Brunei.